2012
DOI: 10.4314/bcse.v27i1.3
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on <i>Pleurotus ferulae</i> potential for the sorption of Pb(II) from aqueous solution

Abstract: ABSTRACT. Pleurotus ferulae obtained from rotten tree was collected, washed, dried, ground and sieved to appropriate particle size. Infra-red spectrometry was used to determine functional groups on the biomass while biosorption of Pb(II) from aqueous solution was studied using the biomass in a batch system. The effect of pH (1-7.5), temperature (30-50 o C), biomass dosage of 0.5-4 g and initial metal concentration (20-300 mg/L) was studied. Equilibrium, kinetics and thermodynamics consideration were evaluated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Cu(II) removal sharply increased from 38.21% at pH 2.0 to 81% at pH 5.0 in P. cornucopiae as reported by Danış ( 2010 ). The maximum biosorption of Pb(II) by P. ferulae with pH up to 3, temperature 30°, and initial metal concentration 100 mg/l has been reported by Adebayo ( 2013 ). Optimum biosorption of divalence cations [Ni(II) and Cu(II)] by Pleurotus mushroom SMS has also been reported to be between pH of 5 and 6 (Tay et al 2012 ).…”
Section: Factors Affecting the Biosorption Processmentioning
confidence: 83%
“…Cu(II) removal sharply increased from 38.21% at pH 2.0 to 81% at pH 5.0 in P. cornucopiae as reported by Danış ( 2010 ). The maximum biosorption of Pb(II) by P. ferulae with pH up to 3, temperature 30°, and initial metal concentration 100 mg/l has been reported by Adebayo ( 2013 ). Optimum biosorption of divalence cations [Ni(II) and Cu(II)] by Pleurotus mushroom SMS has also been reported to be between pH of 5 and 6 (Tay et al 2012 ).…”
Section: Factors Affecting the Biosorption Processmentioning
confidence: 83%
“…It's believed that exposure to heavy metal can be harmful for human health even at the trace level 1 . Therefore, finding useful methods and applying them efficiently have always been vital 2,3 .…”
Section: Introductionmentioning
confidence: 99%
“…K f value of Pisum sativum was higher than Solanum tuberosum which indicated that Pisum sativum had more adsorption capacity for removal of Congo Red dye[31][32][33] Isothermal parameters for removal of Congo Red dye on Solanum tuberosum peels (STP) andPisum sativum peels (PSP).…”
mentioning
confidence: 99%